ظاهرة المشكلات الصوتية لدى الطلاب المادوريين في معهد الأمين الإسلامي سومنب (دراسة تحليلية وصفية) - Achmad Ainul Yaqin Amrullah (Shaut al Arabiyyah, 2023)
This research aims to know the phonetic problems in pronouncing the Arabic word among the students of Al-Ameen Islamic Institute, Gulu-Gulu Sumb, its factors and how to treat it. The methodology of this scientific research is based on the qualitative field research perspective and its descriptive approach to the type of study of the phenomenon. The field of research is the Al-Ameen Islamic Institute, Sumneb. The method of data collection is: 1. Interview 2. Note 3. documents. The method of analyzing the data is: taking care of the data, classifying and describing it, then searching for causes and solutions. As for the results of this research, the researcher can be summarized as follows: (1) Phonetic problems among Madurese students at Al-Ameen Islamic Institute consist of: letter substitution, letter deletion, and letter distortion. (2) The factors affecting these errors consist of: (a) social factors: language interference and the students’ environment. (B) Psychological factors: Affective variables of students. (c) Cognitive factors: communication strategy. (3) The methods for treating phonemic errors and applying them are: (a) To be with the teacher the ability to pronounce the Arabic word and the first language of the students with the correct pronunciation of its letters and to present a model of correct pronunciation of good sounds. (b) Students should know the importance of pronunciation of the Arabic word and pay great attention to it, with examples, with many exercises outside the classroom, and listening a lot. (C) That the Al-Ameen Islamic Institute carry out a training program for teachers of the Arabic language.